Dampak Sosial Ekonomi dan Lingkungan Akibat Runtuhnya Jembatan Kutai Kartanegara - Wiryawan, Bangkit A (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2013)
Kutai Kartanegara Bridge is vital transportation infrastructure that connects Kutai Kartanegara Regency with Samarinda City and its surrounding. The collapse of the bridge in the late 2011 brought wide impact on the mobility of Kutai Kartanegara people. This paper explores social, economic, and environmental impacts that arose from the change of mobility. Generally, respondent activities were not disrupted by the incident, much to do with rapid adaptation capacity of the people and the availability of alternative facilities replacing the bridge. Nonetheless, there are several changes including the intensity of their activity in several sectors such as trade and mining, the emergence of new river crossing service, and the drastically diminishing activities of tourism near the bridge. The emergence of social, economic and environmental impacts should be managed properly to prevent bigger loss.